Variation of Surface Radiocarbon in the North Pacific During Summer Season 2004–2016. Issue 5 (October 2019) - Aramaki, T; Nakaoka, S; Terao, Y; Kushibashi, S; Kobayashi, T; Osonoi, Y; Mukai, H; Tohjima, Y
ABSTRACT: Surface radiocarbon (Δ 14 C) in the North Pacific has been monitored using a commercial volunteer observation ship since the early 2000s. Here we report the temporal and spatial variations in Δ 14 C in the summer surface water when the surface ocean is vertically stratified over a 13-yr period, 2004–2016. The long-term Δ 14 C decreasing trend after the late 1970s in the subtropical region has continued to the present and the rate of decrease of the Kuroshio and Kuroshio Extension, North Pacific and California current areas is calculated to be –3.3, –5.2 and –3.3 ‰/yr, respectively. After 2012 the Δ 14 C of the Kuroshio and Kuroshio Extension area, however, has remained at an approximately constant value of around 50‰. The result may indicate that subtropical surface Δ 14 C in the western North Pacific has reached an equilibrium with atmospheric Δ 14 CO2 . The Δ 14 C in the subarctic region is markedly lower than values in the subtropical region and it seems that the decreasing tendency of surface Δ 14 C has changed to an increasing tendency after 2010. The results may indicate that bomb-produced 14 C, which has accumulated below the mixed layer in the past few decades, has been entrained into the surface layer by deep convection.